Parental Financial Teaching and Youth Financial Literacy: The Role of Family Business Background in Indonesia - I Gusti Bagus Yosia Wiryakusuma; Natania Ken Anniko Giamanto; Yemima Chelsea Kyoko Atmadja (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This research endeavors to examine the differences in parental financial teaching (PFT) and financial literacy (FIL) between individuals with family-business backgrounds and those without in Indonesia. Methodology: Data from 542 respondents, collected via an online questionnaire, were compared using descriptive statistics and independent t-tests. Results: The analysis showed that parental financial teaching (PFT) in family-business is higher; however, financial literacy (FIL) between the two groups is not significantly different. Findings: Research proved that a family-business environment fosters more intensive financial socialisation. Nevertheless, this does not lead to significant differences in financial literacy. Novelty: This research integrates the financial literacy variable and parents parental pedagogical practices into a single empirical framework that accommodates differences in family backgrounds. Originality: This study's original findings in Indonesia challenge the assumption that greater parental financial teaching in family businesses automatically results in higher financial literacy. Conclusion: This research examines the difference in financial teaching and financial literacy between family-business backgrounds and non-family-business backgrounds. The results show that even though financial teaching is higher in family-business, financial literacy in the two groups is not significantly different. Type of Paper: Research paper.